Програма деміфологізації Р. Бультмана і відповідь католицької теології - Пальчик, А. (Світогляд - Філософія - Релігія, 2011)
“Програма деміфологізації” Нового Завіту Р. Бультмана зустрілася з поважною критикою у католицькому теологічному середовищі. Незважаючи на суперечність багатьох ідей дослідника з вченням Церкви, католицька біблеїстика не відкидає методології Бультмана, але наголошує на внесенні принципових коректив. The program of the New Testament demythologization of German Protestant theologian R. Bultmann (1884–1976) clashed with valid criticism in Catholic theological environment. Despite the many contradictory ideas of the researcher with the teachings of the Church, the Catholic biblical studies doesn’t reject Bultmann’s methodology, but lays emphasis on fundamental amending, especially the definition and the role of myth and underlining the historicity of Jesus Christ’s figure in the Gospel.